Transaminase Enzyme and Liver Histopatological Structure of Mice Facing to Smoke Cigarettes After Administerred with Enhalus acoroides Peel Extract (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2023)
The objective of this research were aimed to determine the level of transaminase enzymes and the histopathological structure of mice liver exposed to cigarette smoke after treatment of E. acoroides peel extract. Completely randomized design was conducted with 3 doses treatment groups (P1, P2, P3) and a control group (K+, K-) with 3 times repeated. The test was carried out during 14 days for cigarette smoke, and 14 days for seagrass peel extract tretment. The data measured were the levels of SGOT, SGPT and were analyzed using the Anova test. Liver histopathology (necrosis, parenchymatous, hydropic degeneration and normal) were described descriptively. The results showed that the administration of seagrass E. acoroides peel extract had a significant effect on decreasing levels of SGOT, SGPT (p value 0.05) when compared with K+. The P3 treatment had lower levels of SGOT (80.07±3.1 IU/L) and SGPT (88.3±2.1 IU/L). Liver histopathology consist of 34 necrosis cells less than the positive control group (K+) and normal cells were 47, higher than the positive control group (K+). It can be concluded that E. acoroides peel extract had a significant effect on SGOT, SGPT levels in mice exposed to cigarette smoke. Peel extract of E. acoroides 75 mg/kgBW (P3) was an effective dose to reduce the levels of SGOT, SGPT and improve the histopathological structure of mice liver exposed to cigarette smoke. This research is expected to be useful for the community, especially in the coastal areas regarding the benefits of using E. acoroides as a therapeutic agent against free radicals originating from cigarette smoke.